Developing a digital psychosocial support program for men with low-risk prostate cancer during active surveillance - Kim Donachie; Michel Hansma; Marian Adriaansen; Erik Cornel; Esther Bakker; Lilian Lechner (Internet Interventions)
Background: Active surveillance (AS) is a preferred treatment for men with low- to intermediate-risk prostate cancer, but its psychosocial impact presents challenges. This study used design thinking to develop a digital psychosocial support program aimed at improving quality of life and health outcomes for men on AS. Methods: The design process followed five phases: Empathy, Define, Ideate, Prototype, and Test. Stakeholder interviews were conducted to generate a problem statement. Brainstorming in the ideation phase conceptualized a self-management application and a framework of the application's features was developed. A prototype was developed in close collaboration with end-users and experts. The testing phase included heuristic evaluations and feedback from patients and healthcare providers. Results: Interviews during the empathy phase highlighted the need for personalized care, timely information, and holistic and tailored support. The defined problem statement aimed at reducing the psychosocial burden and improving coping mechanisms during the first year of AS. Ideation involved multidisciplinary brainstorming sessions, resulting in the concept of a self-management application with features such as information, appointment preparation, self-reporting of medical results, lifestyle guidance, relaxation exercises, and communication tools. A prototype application was developed. Testing showed strengths in navigation and design, with recommendations for improving error handling and help documentation. Feedback led to refinements enhancing usability and clinical integration. Conclusion: This study developed a patient-centered self-management application to address psychosocial challenges in AS. By fostering engagement, self-efficacy, and communication, the tool aims to improve outcomes in prostate cancer management. Future clinical studies will evaluate its effectiveness.